Ubiquitin‐specific peptidase 39 promotes human glioma cells migration and invasion by facilitating ADAM9 mRNA maturation - Yue Xiao; Wenjing Ma; Weiwei Hu; Qianqian Di; Xibao Zhao; Xingyu Ma; Xinyi Chen; Ping Sun; Han Wu; Zherui Wu; Weilin Chen (Molecular Oncology, 2022)
Glioma cells are characterized by high migration and invasion ability; however, the molecular mechanism behind both processes still remains to be investigated. Several studies have demonstrated that ubiquitin‐specific protease 39 (USP39) plays an oncogenic role in various cancer types. Here, we investigated the expression and function of USP39 in patients with glioma. Oncomine database analysis revealed that high USP39 expression was significantly correlated with poor overall survival in patients with glioma. Knockdown of USP39 in U251 and U87 cell lines significantly inhibited their migration and invasion in vitro. Gene expression profiling of glioma cells transduced with short hairpin RNA (shRNA) against USP39 revealed that disintegrin and metalloproteinase domain‐containing protein 9 (ADAM9), a molecule previously related to tumor cell migration and invasion, was significantly downregulated. Furthermore, USP39 induced ADAM9 messenger RNA (mRNA) maturation and decreased the expression of integrin β1. Additionally, overexpression of ADAM9 inhibited the migration and invasion of glioma cells caused by USP39 depletion in vitro. USP39 promoted the invasion of glioma cells in vivo and reduced the overall survival of the mice. Altogether, our data show that USP39 induces mRNA maturation and elevates the expression of ADAM9 in glioma cells and may thus be considered potential target for treating patients with glioma.